A retrospective study of imaging characteristics of mucinous tubular and spindle cell carcinoma in the kidney - Wang, Hong; Peng, Xiaoyan; Li, Lutong; Yang, Yujia (Frontiers in Oncology, 2025)
PurposeTo strengthen the recognition of mucinous tubular and spindle cell carcinomas of the kidney (MTSCC) by analyzing ultrasound and computed tomography findings.Materials and methodsThis study retrospectively enrolled eleven patients with pathologically confirmed mucinous tubular and spindle cell carcinomas from 2007 to 2022. The clinical, imaging, pathological features, and prognosis of all included patients were analyzed. All imaging features were evaluated in consensus by two genitourinary radiologists.ResultsAll patients (48 ± 17 years, male to female, 3:8) presented with a solitary renal tumor with a mean diameter of 6.3 cm. Most of the lesions were located in the renal cortex. In ultrasonography, all 11 patients underwent conventional ultrasound and color Doppler flow imaging, and only three underwent contrast-enhanced ultrasound. In computed tomography (CT) examination, 8 of the 11 patients underwent plain CT and contrast-enhanced CT, and 1 patient underwent plain CT only. Grayscale ultrasound image demonstrated that most of the lesions were homogeneously hypoechoic with clear boundaries and regular shapes. Color Doppler flow imaging showed spotty blood flow in some cases. Contrast-enhanced ultrasound showed heterogeneous mild enhancement, and the contrast agent showed ‘slow in and simultaneous/fast out’ pattern. Plain CT showed equal or low density. CECT scanning showed slight heterogeneous enhancement in 6 patients, mild homogeneous enhancement in 2 patients. All lesions showed no hemorrhage, cystic degeneration or necrosis. Contrast-enhanced CT and contrast-enhanced ultrasound showed typical low-vascular tumors.ConclusionMTSCC are more common in middle-aged with a significant female preponderance. CT and ultrasound showed hypovascular tumors. Preoperative imaging diagnosis is difficult. It is necessary to distinguish from other hypovascular renal tumors.multimodal imaging may be helpful for preoperative diagnosis.